Conservation of rare and cryptic species: Challenges of uncertainty and opportunities for progress. Issue 11 (6th October 2022) - Martin, Marie E.; Delheimer, Matthew S.; Moriarty, Katie M.; Early, Desiree A.; Hamm, Keith A.; Pauli, Jonathan N.; Mcdonald, Trent L.; Manley, Patricia N.
Abstract: Effective conservation of at‐risk species presents a conundrum, often requiring rapid status assessments and timely actions regardless of the adequacy of best available information. Here, we present a case study on Humboldt martens ( Martes caurina humboldtensis ), a rare and cryptic carnivore listed as threatened in 2020 under the United States Endangered Species Act. Given their rarity, many aspects of Humboldt marten population ecology remain understudied. To help inform marten conservation, we conducted exploratory analyses to estimate population growth by incorporating empirically derived data into two demographic modeling approaches. Population growth rates from each approach exhibited substantial variability and were uninformative to evaluating population status. Our results highlight the inherent difficulties of studying cryptic animals and exemplify the issues of using sparse or uncertain data in potentially consequential circumstances. Considering the shortcomings of our findings, we provide a framework of reliable actions to improve future conservation outcomes for poorly‐understood species. Abstract : We modeled population growth of a state endangered and federally threatened carnivore, the Humboldt marten, population in northern California, incorporating empirical demographic data under a variety of scenarios, but all scenarios indicated substantial variability in population growth trajectories as an artifact of highly variable survival estimates. Our work exemplifies the issues of using sparse data to inform conservation decisions. We suggest increased collaboration, purposeful study designs, standardized protocols, emerging technologies, and data sharing via public repositories are reliable actions that can produce biologically relevant results and inform future conservation efforts.